LINGUISTIC RULES BASES REDUCTION BASED ON DECISION TREES - Gofman, E.O.; Oliinyk, A.O.; Subbotin, S.O. (Radio Electronics, Computer Science, Control, 2012)
The problem of linguistic rules induction is considered. A method of decision trees identification for linguistic rules induction is developed. The software based on the proposed method is created. Experiments on the solution of practical problems, which allowed to investigate the effectiveness of the proposed method are made.